2019
DOI: 10.1093/ejcts/ezz252
|View full text |Cite
|
Sign up to set email alerts
|

Elastomeric cardiopatch scaffold for myocardial repair and ventricular support

Abstract: OBJECTIVES Prevention of postischaemic ventricular dilatation progressing towards pathological remodelling is necessary to decrease ventricular wall deterioration. Myocardial tissue engineering may play a therapeutic role due to its capacity to replace the extracellular matrix, thereby creating niches for cell homing. In this experimental animal study, a biomimetic cardiopatch was created with elastomeric scaffolds and nanotechnologies. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…This 3D poly-(ethylene glycol) diacrylate (PEGDA)based scaffold obtained by micro-stereolithography promoted human cardiac progenitor cell 3D spatial orientation and activation of the expression of α-sarcomeric actinin and connexin 43 [44•]. As a further example, a cardiopatch manufactured using porous elastomeric polycaprolactone (PCL) 3D membrane filled with self-assembling peptide hydrogel and seeded with autologous adipose tissue-derived progenitor cells improves myocardial infarct scars in sheep [45].…”
Section: Cell Delivery and The Development Of Biomaterial-based Technmentioning
confidence: 99%
“…This 3D poly-(ethylene glycol) diacrylate (PEGDA)based scaffold obtained by micro-stereolithography promoted human cardiac progenitor cell 3D spatial orientation and activation of the expression of α-sarcomeric actinin and connexin 43 [44•]. As a further example, a cardiopatch manufactured using porous elastomeric polycaprolactone (PCL) 3D membrane filled with self-assembling peptide hydrogel and seeded with autologous adipose tissue-derived progenitor cells improves myocardial infarct scars in sheep [45].…”
Section: Cell Delivery and The Development Of Biomaterial-based Technmentioning
confidence: 99%
“…This positive chamber remodeling should contribute to improve diastolic filling and myocardial conditions by angiogenic, antiapoptotic and regenerative mechanisms. Preclinical studies in 18 sheep demonstrated that a cardiopatch manufactured using porous elastomeric polycaprolactone (PCL) 3D membrane filled with peptide hydrogel and stem cells improves myocardial infarct scars [71]. PCL elastomer was chosen for its good mechanical properties, namely flexibility and adaptation to curved surfaces, such as those of ventricles.…”
Section: D Bioprinting Of Functional Myocardiummentioning
confidence: 99%
“…Before translation to human trials can occur, preclinical animal studies are needed. Preclinical in vivo models pursuing regeneration of the myocardium have been reported in pigs 5 , sheep 14 , rats 6 and mice 4 . A common model of myocardial infarction (MI) in mice uses permanent ligation of the left anterior descending (LAD) coronary artery 15 , 16 .…”
Section: Jovecommentioning
confidence: 99%
“…While large animals still represent a more clinically relevant model to test cardiac regenerative properties 5 , 14 , the versatility and feasibility of the mouse model lends itself to this fast-moving area of study. This may avoid some of the pitfalls typical of large animal studies, including (but not limited to): 1) high animal mortality (unless diagonal coronary arteries are ligated leading to unpredictable segmental infarcts 14 , or the distal end of the LAD is occluded followed by reperfusion instead of permanent ligation 5 ); 2) ethical issues with the relatively increased harm caused by large animal protocols compared to mice 18 ; 3) increased cost and/or feasibility issues, for instance the relative unavailability of large animal equipment such as MRI scanners 14 . It is also important to consider that given the extensive duration and commitment typical of large animal studies, they have the potential to become outdated before they are finished, especially with the rapid developments typical of this field.…”
Section: Jovecommentioning
confidence: 99%
See 1 more Smart Citation